Association between school bullying and self-harm in Chinese children and adolescents: the mediating role of mindfulness - Changlin Zhang; Fang Liu; Hailiang Ran; Yusan Che; Die Fang; Shuqing Liu; Guiqing Zheng; Yandie He; Yi Xiang; Jin Lu; Yuanyuan Xiao (BMC Public Health)
Abstract Background Non-suicidal self-injury (NSSI) poses a significant challenge to the health and well-being of children and adolescents, with prior studies suggesting a strong association with experiences of school bullying. While mindfulness has been identified as a protective factor against NSSI, its mediating role in the relationship between school bullying and NSSI remains insufficiently investigated. Using a representative sample from Yunnan Province, China, this study aims to contribute to the understanding of the relationship between school bullying, NSSI, and mindfulness. Methods A population-based sample of 5897 adolescents in two places of Yunnan Province were surveyed by using self-administered questionnaires. Logistic regression model was used to measure the association between school bullying and NSSI. Path model was further fitted to examine the mediation of mindfulness in the association between school bullying and NSSI. Results The lifetime NSSI prevalence in our study sample was 34.6% (95% CI: 30.3%–39.0%). School bullying was associated with an increased risk of NSSI (OR = 2.02, 95% CI: 1.68–2.43), while a higher mindfulness score was associated with a reduced NSSI risk (OR = 0.98, 95% CI: 0.97–0.99). Path analysis showed mindfulness significantly mediated the relationship between school bullying and NSSI, accounting for 34.0% of the total association. Among all dimensions of mindfulness, mindfulness observing, describing, and acting with awareness significantly mediated the association, with acting with awareness showing the strongest mediation. Conclusions The findings indicate a positive correlation between school bullying and NSSI, with mindfulness serving as a significant mediator in this association. Enhancing mindfulness among children and adolescents could be an effective strategy to mitigate school bullying associated NSSI.